Language Standarization In General Point of View - Ramlan, Ramlan (Budapest International Research and Critics University, 2018)
Language has the great roles in human’s lives because it is used as a means of communication among the member of society. Naturally different ethnics of course have the different race, the tribe, and the language. Language is much more than a system of communication, it is a symbolical marker that distinguishes who belongs to a group and who is outside. Language has been traditionally considered as a central feature of ethnic identity and national identity, therefore, the identity and the integrity of a nation is well-showed by a language. Moreover, standardized language is a way to support a common identity. A language should be standardized to get its formality. The processes of language standardization are: selection, codification, elaboration of function, and acceptance.